The Relationship Between Teachers’ Calling, Job Performance, and Organizational Commitment: The Mediating Role of Work-Related Flow Experience - Çalışkan, Yurdanur; Kılınçarslan, Ömür; Efeoğlu, İbrahim Efe (İşletme Araştırmaları Dergisi, 2023)
Purpose - Teachers' work attitudes play an essential role in raising and educating future generations. This study aimed to investigate the effect of teachers' calling on job performance and organizational commitment and the mediating role of work-related flow experience on this effect. Design/methodology/approach- The data was collected through proper surveys received from 377 teachers in Adana. The appropriate data's frequency analysis and factor analysis were done with SPSS 24.0 and SmartPLS 3.3.9 programs, respectively. The Structural Equation Model (PLS-SEM) method was used to determine the path coefficients (hypotheses) and the mediating role of the model created at the second level. Findings-The results have shown that calling positively affects job performance, work-related flow experience, and organizational commitment. The work-related flow experience positively affects job performance and organizational commitment. While the partial mediating role of work-related flow experience in the relationship between calling and job performance was affirmed, the mediating role of work-related flow experience in the relationship between calling and organizational commitment could not be confirmed. Discussion– Teachers with positive attitudes and behaviors towards their profession have trained qualified human resources in the educational system. Teachers who have a calling sense could experience work-related flow experience under suitable conditions, and this could positively affect both their job performance and organizational commitment. Therefore, a supportive environment with managerial and peer support should be created in schools for teachers to find their work more meaningful and increase their calling and work-related flow experiences.